Incidence and predictors of intraoperative hypertension during laparoscopic cholecystectomy for acute cholecystitis: retrospective cohort study - Elsheikh, Mohamed; Abdelkhalik, Sameh; Eid, Ahmed; Barakat, Hosam (International Surgery Journal, 2024)
Background: The authors noticed during their practice that most of patients scheduled for laparoscopic cholecystectomy (LC) owing to acute cholecystitis are associated with increased intraoperative blood pressure especially during manipulation on the gallbladder which may increase the risk of bleeding. A retrospective analysis was carried out to estimate the risk and the potential risk factors of intraoperative hypertension. Methods: A retrospective analysis of the data of patients who underwent LC for acute cholecystitis in our university hospitals from June 2022 to December 2023. The patients’ documents and records were revised with exclusion of patients with incomplete data. The data of age, gender, ASA class, BMI, co-morbidities, preoperative CRP, preoperative TLC, preoperative temperature, and preoperative bilirubin were collected and reported. The data of duration of surgery, time for devascularization of the gallbladder, and the changes in the blood pressure were also recorded. Results: Seventy-three patients underwent LC for acute cholecystitis during the study period, 44 (60.27%) of them developed intraoperative hypertension with statistically significant difference between the patients who did not develop intraoperative hypertension in BMI (p=0.0003), preoperative CRP (p=0.008), preoperative TLC (p=0.001), duration of surgery (p=0.034), and time to devascularization of the gallbladder (p=0.027). The regression analysis revealed an increased risk of intraoperative hypertension with decreased age (p=0.0191), increased BMI (p=0.034), and increased preoperative TLC (p=0.038). Conclusions: The risk of intraoperative hypertension during LC for acute cholecystitis increased with decreased age, increased BMI, and increased preoperative TLC.